Brittle cornea syndrome: current perspectives [Letter] - Srirampur A (Dove Medical Press, 2019)
Arjun Srirampur, Shalini Kumari Agrawal, Veerendranath Pesala Anand Eye Institute, Hyderabad 500007, IndiaCorrespondence: Arjun SrirampurAnand Eye Institute, Nagendranagar Colony, Hyderabad 500007, IndiaTel +91 998 922 9832Fax +91 040 2 715 1999Email sarjuneye@gmail.com I have read with great interest the review article by Walkden et al on “Brittle Cornea Syndrome: Current Perspectives”.1 I would like to express my appreciation to the authors for an elaborate and comprehensive review of this complex disease which has devastating complications. I agree with the authors on various surgical techniques to manage the eyes with brittle cornea syndrome(BCS).I have managed a few children with BCS in our hospital with spontaneous corneal ruptures after a trivial trauma. Based on our experience, I would like to add a few surgical tips in managing a corneal tear in patients with BCS. View the original paper by Srirampur A and colleagues